A case of Epstein-Barr virus–associated hemophagocytic lymphohistiocytosis with severe cardiac complications. Issue 1 (December 2016) - Kawamura, Yoshiki; Miura, Hiroki; Matsumoto, Yuji; Uchida, Hidetoshi; Kudo, Kazuko; Hata, Tadayoshi; Ito, Yoshinori; Kimura, Hiroshi; Yoshikawa, Tetsushi
Abstract Background Hemophagocytic lymphohistiocytosis (HLH) is a life threatening hematological disorder associated with severe systemic inflammation caused by an uncontrolled and ineffective immune response resulting in cytokine storm. Epstein-Barr virus (EBV) is the most common infectious agent in patients with the viral-associated HLH. Limited numbers of cases with cardiac complication have been demonstrated in other viral-associated HLH patients. Herein, we report a pediatric case of severe EBV-associated HLH with cardiac complications. Case presentation A previously healthy 4-year-old Japanese female was admitted to a local hospital with a four day history of fever. Despite antibiotic treatment, her fever persisted to day 7 of the illness. Finally, the diagnosis of HLH was confirmed by fulfilling diagnostic criteria for HLH and pathological analysis of bone marrow aspiration. Real-time PCR detected a high copy number of EBV DNA in the peripheral blood mononuclear cells (PBMCs) at the time of hospital admission. During treatment according to HLH-2004 protocol, sudden cardiopulmonary arrest (CPA) occurred on day 30 of the illness and immediate resuscitation was successful. Acute myocarditis was considered the cause of the CPA. Although the treatment regimen was completed on day 88 of the illness, a remarkably high copy number of EBV DNA was still detected in her PBMCs. Based on our flow cytometric in situ hybridization analysis that revealed EBV infection of only B lymphocytes, we decided to administer rituximab to control the abnormal EBV infection. Afterwards the amount of EBV DNA decreased gradually to undetectable level on day 130 of the illness. Unfortunately, a coronary artery aneurysm was discovered at the left main coronary artery on day 180 of the illness. Finally, the patient was discharged from the hospital on day 203 of the illness without sequelae except for a coronary aneurysm. Conclusions In this case report, EBV-HLH was complicated with cardiac symptoms such as myocarditis and coronary artery aneurysm. Although remarkably high copy number of EBV DNA was detected in PBMCs after completion of the HLH-2004 protocol, rituximab treatment resulted in a dramatic decrease of EBV DNA to undetectable levels. Rituximab treatment might have been beneficial for the patient's survival.